Is the Phenotype Designation by PSP-MDS Criteria Stable Throughout the Disease Course and Consistent With Tau Distribution? - Sánchez-Ruiz de Gordoa, Javier; Zelaya, Victoria; Tellechea-Aramburo, Paula; Acha, Blanca; Roldán, Miren; López-Molina, Carlos; Coca, Valle; Galbete, Arkaitz; Mendioroz, Maite; Erro, M. Elena (Frontiers in Neurology, 2022)
Introduction:The MDS-PSP criteria have shown high sensitivity for the PSP diagnosis, but do not discriminate the phenotype diversity. Our purpose was to search for anatomopathological differences among PSP phenotypes resulting from the application of the MDS-PSP criteria comparing with the previous ones. Methods:Thirty-four PSP cases from a single brain bank were retrospectively classified according to the criteria used by Respondek et al. in 2014 and the PSP-MDS criteria at 3 years (MDS-3y), 6 years (MDS-6y) and at the last clinical evaluation before death (MDS-last). Semiquantitative measurement of total, cortical and subcortical tau load was compared. For comparative analysis, PSP-Richardson syndrome and PSP postural instability were grouped (PSP-RS/PI) as well as the PSP atypical cortical phenotypes (PSP-Cx). Results:Applying the Respondek´s criteria, PSP phenotypes were distributed as follow: 55.9% PSP-RS/PI, 26.5% PSP-Cx, 11.8% PSP-Parkinsonism (PSP-P), and 5.9% PSP-Cerebellum. PSP-RS/PI and PSP-Cx had a higher total tau load than PSP-P; PSP-Cx showed a higher cortical tau load than PSP-RS/PI and PSP-P; and PSP-RS/PI had a higher subcortical tau load than PSP-P. Applying the MDS-3y, MDS-6y and MDS-last criteria; the PSP-RS/PI group increased (67.6%, 70.6% and 70.6% respectively) whereas the PSP-Cx group decreased (8.8%, and 8.8% and 11.8%). Then, only differences in total and subcortical tau burden between PSP-RS/PI and PSP-P were observed. Interpretation:After the retrospective application of the new MDS-PSP criteria, total and subcortical tau load is higher in PSP-RS/PI than in PSP-P whereas no other differences in tau load between phenotypes are found, as a consequence of the loss of phenotypic diversity.